Controllable synthesis of in situ grown titanate hierarchical microspheres and subsequent chemical modifications for superhydrophobic and oil–water separation properties. Issue 19 (17th March 2020) - Li, Yong; Xie, Jiyang; Guo, Changjin; Wang, Jian; Liu, Huan; Hu, Wanbiao
Abstract : An in situ "nucleation-cum-growth" solution chemistry strategy was performed to synthesize titanate hierarchical microspheres with superhydrophobic properties and oil–water separation performance. Abstract : Sodium titanate nanowire-assembled microspheres on titanium mesh have been synthesized through controlling an over the surface acidification and hydrothermal process in terms of a proposed in situ "nucleation-cum-growth" solution chemistry strategy. These directly grown microspheres crystallize in an orthorhombic lepidocrocite layered structure of sodium titanate with the composition of Na1.8 Ti1.95 □0.05 O4.8 (□ ∼ vacancy) determined by the XRD, Raman and SEM-EDX techniques. An individual microsphere has a uniform size of around 10 microns while the constituent nanowires have a diameter of 100 nm growing along the [110] orientation. Owing to the specially well-defined hierarchical structure and robust in situ interfaces, these titanate nanowire-assembled microspheres, after 2, 2, 3, 3, 4, 4, 5, 5-octafluoro-1-pentanol (OFP) surface modification, could achieve superhydrophobicity. This work demonstrates an in situ "nucleation-cum-growth" synthesis strategy and facile functionalization towards superhydrophobicity for oil–water separation, which might extend to a broad variety of oxide nanowire systems to fabricate well-defined structures for wettability tailoring and multi-functional applications.